Measuring molecular frequencies in the 1–10 μm range at 11-digits accuracy. Issue 1 (December 2017) - Insero, G.; Borri, S.; Calonico, D.; Pastor, P.; Clivati, C.; D'Ambrosio, D.; Natale, P.; Inguscio, M.; Levi, F.; Santambrogio, G.
Abstract High-resolution spectroscopy in the 1–10 μm region has never been fully tackled for the lack of widely-tunable and practical light sources. Indeed, all solutions proposed thus far suffer from at least one of three issues: they are feasible only in a narrow spectral range; the power available for spectroscopy is limited; the frequency accuracy is poor. Here, we present a setup for high-resolution spectroscopy, whose approach can be applied in the whole 1–10 μm range. It combines the power of quantum cascade lasers (QCLs) and the accuracy achievable by difference frequency generation using an orientation patterned GaP crystal. The frequency is measured against a primary frequency standard using the Italian metrological fibre link network. We demonstrate the performance of the setup by measuring a vibrational transition in a highly-excited metastable state of CO around 6 μm with 11 digits of precision.